2023
DOI: 10.21203/rs.3.rs-2631478/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pilot Scale Tannin Extraction from Chestnut Wood Waste using Hydrodynamic Cavitation

Abstract: Tannins, extracted from various plant sources, are worldwide commodities used in several different fields, including leather manufacturing and the production of bio-based adhesives, with emerging use in technical, environmental, food and feed sectors, pharmacology. Due to increasing market demand, few emerging techniques were proposed besides the usual hot water extraction usually performed under pressurized conditions. For the first time, hydrodynamic cavitation, an emerging and straightforwardly scalable gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Compounds 41 and 46, with a [M-H] − ion at m / z 785 were tentatively identified as tellimagrandin I and tellimagrandin I isomer, according to a previous work . Finally, according to their mass spectra and the previous literature, , several trigalloyl glucose ( 37 , 40 , 42 – 45 ), tetra-galloyl glucose ( 47 – 49 and 51 – 52 ), and penta-galloyl glucose derivatives ( 54 – 55 ) were tentatively identified. Compounds 56 and 57 were tentatively identified as ellagic acid derivatives such as ellagic acid deoxyhexose and dehydrated ellagic acid dimer, respectively.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Compounds 41 and 46, with a [M-H] − ion at m / z 785 were tentatively identified as tellimagrandin I and tellimagrandin I isomer, according to a previous work . Finally, according to their mass spectra and the previous literature, , several trigalloyl glucose ( 37 , 40 , 42 – 45 ), tetra-galloyl glucose ( 47 – 49 and 51 – 52 ), and penta-galloyl glucose derivatives ( 54 – 55 ) were tentatively identified. Compounds 56 and 57 were tentatively identified as ellagic acid derivatives such as ellagic acid deoxyhexose and dehydrated ellagic acid dimer, respectively.…”
Section: Resultssupporting
confidence: 90%
“…Meneguzzo et al proposed 100 °C as the maximum extraction temperature for a cavitation process to guarantee an accelerated tannin release. These results, even if obtained under experimental conditions different from those applied in our work, confirmed that 100 °C is a good choice as an extraction temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The forest area of the Parco del Respiro is managed for recreational purposes with the active maintenance of paths, the removal of standing dead trees and lying deadwood for safety reasons, and the cleaning of grasslands. In addition, Meneguzzo and Zabini [30] highlighted that this forest site has an average VOC concentration of 38 parts per billion (ppb) and a maximum VOC concentration of 108 ppb. These values are quite high compared to other sites studied by those same authors [30]: Ligonchio in the Apennines (i.e., average VOC 10 ppb with a peak of 20 ppb); Fonte del Borbotto near the Foreste Casentinesi Park, Tuscany (i.e., average VOC 15 ppb with a peak of 30 ppb); and Villa Vogel urban park in Florence city, Tuscany (i.e., average VOC 15 ppb with a peak of 56 ppb).…”
Section: Study Areamentioning
confidence: 99%
“…The selected study area is the Parco del Respiro in the Trentino-Alto Adige region. The Parco del Respiro has been set up for forest bathing activities since 2019, and previous research has quantified a high concentration of total volatile organic compounds (TVOCs) suitable for producing positive effects on human health within the park [29,30]. For these reasons, the Parco del Respiro is chosen as a representative site for forest bathing, where it would be effective to experiment with the application of an economic method (i.e., TCM) yet to be adopted for the estimation of the forest bathing value.…”
Section: Introductionmentioning
confidence: 99%